Sheet metal forming processes and die design - Boljanovic, Vukota (Books24x7.com, 2005)
Annotation Written by an engineer with decades of practical manufacturing experience, this book is a complete modern guide to sheet metal forming processes and die design-still the most commonly used methodology for the mass-production manufacture of aircraft, automobiles, and complex high-precision parts. It illustrates several different approaches to this intricate field by taking the reader through the "how's" and "why's" of product analysis, as well as the techniques for blanking, punching, bending, deep drawing, stretching, material economy, strip design, movement of metal during stamping, and tooling. While concentrating on simple, applicable engineering methods rather than complex numerical techniques, this practical reference makes it easier for readers to understand the subject by using numerous illustrations, tables, and charts.
Title from title screen.
Keywords: Sheet-metal work.; Dies (Metal-working); elektronické knihy; electronic books